Acute myeloid leukemia with t(8;21)(q22;q22) preceded by breast granulocytic sarcoma - Rocha Filho,Francisco D. (2008)
Granulocytic sarcoma (GS) is a rare extramedullary tumor mass composed of immature cells derived from the hematopoietic myeloid series. It is usually associated with leukemia and other myeloproliferative disorders but can also occur without overt hematologic diseases. The breast has been reported to be an uncommon site of presentation. We report a case of acute myeloid leukemia preceded by GS of the breast. The immunohistochemistry revealed myeloperoxidase, CD68 and CD43 positivity, thus indicating a diagnosis of GS. Conventional cytogenetic analysis of peripheral blood cells showed t(8;21)(q22;22). Complete remission was achieved with Daunorubicin and Cytarabine induction therapy followed by three courses of high-dose Cytarabine consolidation. The patient remains in continuous complete remission at 27 months.